2007
DOI: 10.1093/ps/86.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Corticosterone Further Reduces the Reproductive Function of Male Offspring Hatched from Eggs Laid by Quail Hens Selected for Exaggerated Adrenocortical Stress Responsiveness

Abstract: Activation of the hypothalamic-pituitary-adrenal (HPA) axis can depress the hypothalamic-pituitary-testicular axis. Male quail cloacal gland (CG) size and foam production shows androgen dependency, and males selected for exaggerated [high stress (HS)] rather than reduced [low stress (LS)] plasma corticosterone (B) stress response exhibit reduced CG and testes development. High stress hens also deposit more B into egg yolks than LS ones, and quail hens given B produce chicks that have a reduced growth rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…While some studies only collected eggs laid 7 days after the beginning of treatment (de la Cruz et al, 1987;Hayward and Wingfield, 2004) others pooled eggs collected over a longer period (Janczak et al, 2007a-day 5-10;Satterlee et al, 2007-day 7-14; Henriksen et al, submitted for publication-day 12-18; Davis et al, 2008-2-3 weeks). The decision on when to collect eggs might be based on the duration of plasma CORT elevation in each single study, but some studies did not measure plasma CORT in the mothers (Rozenboim et al, 2007;Satterlee et al, 2007;Davis et al, 2008), making it difficult to estimate the duration and intensity of maternal CORT elevation during egg formation. The potential differences in duration and intensity of prenatal exposure to maternal stress due to differences in the experimental design between studies might therefore explain some of the inconsistencies seen between studies regarding the offspring's phenotype.…”
Section: Possible Explanation For Inconsistency In Results Between Stmentioning
confidence: 99%
See 4 more Smart Citations
“…While some studies only collected eggs laid 7 days after the beginning of treatment (de la Cruz et al, 1987;Hayward and Wingfield, 2004) others pooled eggs collected over a longer period (Janczak et al, 2007a-day 5-10;Satterlee et al, 2007-day 7-14; Henriksen et al, submitted for publication-day 12-18; Davis et al, 2008-2-3 weeks). The decision on when to collect eggs might be based on the duration of plasma CORT elevation in each single study, but some studies did not measure plasma CORT in the mothers (Rozenboim et al, 2007;Satterlee et al, 2007;Davis et al, 2008), making it difficult to estimate the duration and intensity of maternal CORT elevation during egg formation. The potential differences in duration and intensity of prenatal exposure to maternal stress due to differences in the experimental design between studies might therefore explain some of the inconsistencies seen between studies regarding the offspring's phenotype.…”
Section: Possible Explanation For Inconsistency In Results Between Stmentioning
confidence: 99%
“…Two out of five studies reported a lower hatching mass in offspring of stressed mothers (Love et al, 2005; Henriksen et al, submitted for publication), four out of six studies reported lower body mass later in life (Hayward and Wingfield, 2004;Love et al, 2005; Henriksen et al, submitted for publication; de la Cruz et al, 1987) and none reported an increase in body mass. The two studies that did not find any difference in body mass post hatching between offspring of control and stressed mothers (Janczak et al, 2007a;Satterlee et al, 2007) also did not find any difference in body mass at hatching. Elevated maternal CORT during egg formation therefore seems to have the potential to reduce the prenatal, and especially the postnatal growth of the offspring that hatch from these eggs.…”
Section: Effects On Avian Offspring's Physiologymentioning
confidence: 88%
See 3 more Smart Citations